Optimization of Productive Waqf as a Social Investment Instrument from the Perspective of Islamic Economics - Yundira, Viska; Al Farisi, Muhammad Salman (Sharia Business Management Department of STEBIS Bina Mandiri, 2025)
This study aims to explore how productive waqf can be optimized as a social investment instrument from the perspective of Islamic economics. The research specifically seeks to identify the roles, strategies, and challenges faced by waqf institutions in managing productive waqf assets to enhance community welfare. Using a qualitative approach with a case study method, data were collected through in-depth interviews, field observations, and document analysis at several waqf institutions in Indonesia. The findings reveal that the optimization of productive waqf involves three main aspects: strengthening institutional capacity, applying sharia-based investment principles, and increasing public trust through transparency and accountability. The study also found that productive waqf has a significant impact on financing social and economic programs, empowering small and medium enterprises, and supporting sustainable community development. This research concludes that productive waqf, when managed professionally and in accordance with Islamic economic principles, can serve as an effective social investment instrument, contributing to both social welfare and economic equity.